Changes in Cortisol and in Oxidative/Nitrosative Stress Indicators after ADHD Treatment - Laura Garre-Morata; Tomás de Haro; Raquel González Villén; María Luisa Fernández-López; Germaine Escames; Antonio Molina-Carballo; Darío Acuña-Castroviejo (MDPI AG, 2024)
Although ADHD is one of the most prevalent diseases during childhood, we still do not know its precise origin; oxidative/nitrosative stress and the hypothalamic-pituitary-adrenal axis are suggested contributors. Methylphenidate, among others, is the main drug used in ADHD patients, but its effects on relevant markers and structures remain unclear. This study, involving 59 patients diagnosed with ADHD according to DSM-5 criteria, aimed to assess changes in cortisol levels (using cortisol awakening response, CAR) and oxidative/nitrosative status with the treatment. Blood samples before and 3 months after treatment with methylphenidate were used to measure oxidative and inflammatory markers, as well as the endogenous antioxidant activity, while saliva samples tracked cortisol awakening response (CAR). The results showed a treatment-related improvement in the redox profile, with the reduction in advanced oxidation protein products (AOPP), lipid peroxidation (LPO), and nitrite plus nitrate (NOx) levels, and the increase in the enzymatic activities of glutathione reductase (GRd) and catalase (CAT). Moreover, the area under the curve (AUC) of CAR increased significantly, indicating increased reactivity of the HPA axis. These results support, for the first time, the involvement of the endogenous antioxidant system in the pathophysiology of ADHD.